The Effect of Bridge Piers on Local Scouring at Alue Buloh Bridge Nagan Raya Regency - Cut Suciatina Silvia; Muhammad Ikhsan; Azwanda Azwanda (Journal of the Civil Engineering Forum, 2021)
Scouring that occurs in cross-section a river can be caused by morphological conditions of the river and the effect of bridge piers that obstruct the flow. Availability of piers and abutments can cause the stability of soil base granules to be disrupted, downflow, and horseshoe vortex that causes soil base granules around the bridge pier to be transported the flow that causes occurrence in local scouring. The problems of local scours also occurred in Krueng Ineng river, Alue Buloh Village, Nagan Raya Regency. The problem that is often encountered due to bridges being built across rivers is the lack of functioning of the under-bridge structures. Local scours on the bridge piers will cause a structural collapse which has the impact of decreasing the stability of the bridge structure currently. In this study, local scour analysis are using empirical equations with the Froehlich, Lacey and Colorado State University Method. The Results of the analysis with used the peak discharge (Qp100) that occurs in the Krueng Seunagan watershed is 1513m3/sec. Analysis with a flow depth of 3.06m, Froude number 0.29, pier width with lenticular shaped 4m, and D50, D95 (average grain size analysis ) 0.91mm and 4.35mm, show a maximum scour depth at the field of 1.65m and 1.68m occurs in point (station) 2 and 3 on segment 5. Analysis with the Froehlich, Lacey Method and the CSU Method shows a scour depth is 1.68m, 4,47m (Qp100) and 2.43m. The closest measurement result in the field is the Froehlich Method. With this result, it might be input for local governments to plan appropriate handling for minimizing local scour in this study area